2008
DOI: 10.1007/978-3-540-79309-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Games with Linearly Independent Paths: Convergence Time and Price of Anarchy

Abstract: Abstract. We investigate the effect of linear independence in the strategies of congestion games on the convergence time of best improvement sequences and on the pure Price of Anarchy. In particular, we consider symmetric congestion games on extension-parallel networks, an interesting class of networks with linearly independent paths, and establish two remarkable properties previously known only for parallel-link games. More precisely, we show that for arbitrary (non-negative and non-decreasing) latency functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…We can therefore conclude that the (altruistic) price of anarchy will be a non-increasing function of ρ. This is a remarkable result since, to the best of our knowledge, the classical price of anarchy is unknown (the best lower bound is given by Fotakis [11]). …”
Section: Implications and Additional Insightsmentioning
confidence: 98%
See 2 more Smart Citations
“…We can therefore conclude that the (altruistic) price of anarchy will be a non-increasing function of ρ. This is a remarkable result since, to the best of our knowledge, the classical price of anarchy is unknown (the best lower bound is given by Fotakis [11]). …”
Section: Implications and Additional Insightsmentioning
confidence: 98%
“…Lemma 4 (Fotakis [11] The following lemma gives inefficiency results for global minima of the potential function (compared to any feasible flow). Since the local minima of correspond to the Nash equilibria of the game , it follows that the global minima of are Nash equilibria.…”
Section: Theorem 7 Let Be a Linear Symmetric Network Congestion Gamementioning
confidence: 99%
See 1 more Smart Citation
“…This observation has led to a large amount of work that identified special classes of congestion games, where bestresponse dynamics converge to a Nash equilibrium in polynomial time or even linear time. This agenda has been the focus of [7,11] in a setting with negative congestion effects, and was also studied in a setting of positive congestion effects [2]. In particular, it has been shown that it takes at most n steps (where n is the number of users) to converge to a Nash equilibrium if the network is composed of parallel links [7], and this result has been later extended to extension-parallel networks [11].…”
Section: Measures)mentioning
confidence: 99%
“…This agenda has been the focus of [7,11] in a setting with negative congestion effects, and was also studied in a setting of positive congestion effects [2]. In particular, it has been shown that it takes at most n steps (where n is the number of users) to converge to a Nash equilibrium if the network is composed of parallel links [7], and this result has been later extended to extension-parallel networks [11]. For resource selection games (i.e., where feasible strategies are composed of singletons), it has been shown in [13] that better-response dynamics converge within at most mn 2 steps for general cost functions (where m and n are the number of resources and users, respectively).…”
Section: Measures)mentioning
confidence: 99%